Using Skew Cyclic Codes Over R = R1×R2×R3 to Detect Skew Cyclic Codes Over Fq (Contemporary Mathematics, 2024)
This article investigates linear codes over the ring , focusing on the properties and structure of skew cyclic codes within this framework. We explore various algebraic features of these codes, highlighting their distinctivenessfrom traditional cyclic codes. In addition, we examine the utility ofskew cyclic codes over  in the context of identifying skew cyclic codes over the finite field with optimal parameters. The findings offer fresh perspectives on developing efficient and high-performing coding systems, which could benefit error correction and data transmission applications.
Keywords: linear codes; skew cyclic codes; gray map; optimal codes; automorphism